(untitled) (Palimpsesto, 2021)
Between 1955-1976 Argentina experienced a cycle of growing conflict and social mobilization. In that context, processes of political radicalization emerged that converged with the origin of the organizations of the New Left, who projected an extensive field as a form of intervention in the face of the dilemmas that characterized the time of the sixties. This article recovers from the perspective of intellectual history, the journal Cristianismo y Revolución, published between 1966-1971, by radicalized Catholic intellectuals, with the aim of analyzing the discussions that this editorial group engaged in about the university and the role of the student movement in the face of the national question, in the context of opposition to the dictatorship of the Argentine Revolution, the progressive social upheaval with the accentuated participation of university sectors, the changes crossed by the proscribed Peronism and the complexity of the Catholic world from the actions of the Third World movements.